Material selection in mechanical design of car bumper - Nurul Azwan, Adnan (2009)
This study was carried out to study Material selection in mechanical design of car bumper. The objectives of this study are to perform material selection process to find the best material that can be use as car bumpers material, compare the alternative method with conventional method and use Computer-aided selection software (CES) to find the best process for car bumper manufacturing. Weight property method as alternative method and cost per unit property method as conventional method were performed to find the suitable material for car bumper. After finish selection using weight property method, cost per unit property method was performed. The material selected from these two methods was compared to find the best selected material. The materials performance index, M, were derive basic formula like stiffness and force at fracture. Function of materials performance index, was plotted on the Young’s modulus – density chart and strength – density chart. In weight property method, the material selection was made by referring to the performance index. It was found that Carbon fibre-reinforced polymer (CFRP) was the best material as it has high performance index. The best selected material in cost per unit property method was Magnesium alloys (Mg Alloys) based on the smallest value of cost per unit property. However, due to limitation of cost per unit property method, result is more accurate value to several of attributes. Lastly, Computer Aided selection processes were used to find the suitable manufacturing processes for selected material.